DO INTELLECTUAL CAPITAL AND FIRM SIZE AFFECT PROFITABILITY? EVIDENCE FROM PROPERTY AND REAL ESTATE COMPANIES IN INDONESIA - Ruslina Lisda; Anthony Anthony (JRAK, 2023)
The main objective of establishing a company is to seek profits, Utilizing a combination of tangible and intangible assets is significant to improve financial performance, especially in generating profits. Therefore, this research aims at determining the influence of intellectual capital and firm size on profitability in property and real estate companies listed on the Indonesian stock exchange. The population in this research is property and real estate companies listed on the Indonesian Stock Exchange in 2010-2021 accumulating 82 companies with a total sample of 29 companies. The results showed that partial intellectual capital affected profitability, while firm size did not affect profitability simultaneously, and Intellectual capital and firm size affected profitability. The implication of the research was to provide useful suggestions for companies to find out analyses that could influence profitability.